Modeling for Radial Distribution of Sap Flow in Rubber (Hevea brasiliensis Muell. Arg.) Trees - Kunjet, Sumit; Thaler, Philippe; Gay, Frederic; Chuntuma, Pisamai; Sangkhasila, Kumut; Kasemsap, Poonpipope (Agriculture and Natural Resources, 2014)
This research improved the model for the radial distribution of the sap ﬂux density in rubber trees. The objective of the study was to describe the radial variability of xylem sap ﬂux in rubber trunks. The experiment was conducted in mature rubber trees aged 13 yr from clone RRIM 600, in a non-traditional planting area at the Chachoengsao Rubber Research Center from January to December 2007. The sap ﬂow was measured by the heat dissipation method using home-made radial probes and then calibrated with the cut stems of rubber tree in the laboratory. The radial variability was modeled as a function of the depth into the xylem. Regression analysis was carried out using data on the sap ﬂux density and depth into the xylem. The model used two basic assumptions: (1) young xylem (0–4 cm) has the maximum sap ﬂux density and is stable and (2) sap ﬂux density decreases linearly with the depth into the xylem (and thus older xylem) toward the center of the stem. The results showed that the model for radial distribution can be used to predict the sap ﬂux density and to estimate the tree transpiration of different trunk diameters in rubber trees. The tree transpiration was highly variable with different girths of the rubber trees.